2020
DOI: 10.1088/1757-899x/988/1/012104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of hardness and effect of wear on sintered composites containing AA6061 matrix and TiB2/Al2O3reinforcements

Abstract: Materials prepared using powder metallurgy route exhibit dimensional stability which is required to manufacture critical parts such as brake pads, inlet valves and nozzles. In this paper, composite materials consisting of 5 and 10 wt. % of Titanium-diboride reinforcement in AA6061 aluminium alloy was produced by the sintering process via green compaction. 2 wt. % of alumina was added as the secondary reinforcement to produce the hybrid composites. The produced composites and its hybrid were compared with the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The spacing between these bands is equal to the distance that the tool covers while moving forward in every single rotation. Researchers reported that such macrostructures were formed due to the variation in grain size, particles and the precipitates distribution, crystallographic textures, dislocation density, and the chemistry due to the inter-mixing of the dissimilar alloys [15,[39][40][41][101][102][103][104][105][106][107][108]. Krishnan [109] during FSW of dissimilar AA6061-AA7075 alloys at different welding parameters reported that these variations were caused due to the frictional heat imparted to the material to heat and the forward movement of the rotating tool that extrudes the material about the RS that leads to the formation of the banded structure during the rotational motion of the FSW tool.…”
Section: Banded Structure Formation In Nzmentioning
confidence: 99%
“…The spacing between these bands is equal to the distance that the tool covers while moving forward in every single rotation. Researchers reported that such macrostructures were formed due to the variation in grain size, particles and the precipitates distribution, crystallographic textures, dislocation density, and the chemistry due to the inter-mixing of the dissimilar alloys [15,[39][40][41][101][102][103][104][105][106][107][108]. Krishnan [109] during FSW of dissimilar AA6061-AA7075 alloys at different welding parameters reported that these variations were caused due to the frictional heat imparted to the material to heat and the forward movement of the rotating tool that extrudes the material about the RS that leads to the formation of the banded structure during the rotational motion of the FSW tool.…”
Section: Banded Structure Formation In Nzmentioning
confidence: 99%
“…Examined the results indicating 15% B 4 C is best for machinability and surface characteristics. Raja and Prakash[22] created AA6061/TiB 2 /Al 2 O 3 hybrid metal matrix composite using powder metallurgy.…”
mentioning
confidence: 99%